2016
DOI: 10.4103/0019-5049.195488
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane versus sevoflurane with interscalene block for shoulder arthroscopic procedures: Value of process capability indices as an additional tool for data analysis

Abstract: Background and Aims:Hypotensive anaesthesia reduces intra-articular bleed and promotes visualisation during arthroscopy. The haemodynamic effects of inhalational agents isoflurane and sevoflurane were studied extensively, and both were found to reduce mean arterial pressures (MBP) to an equivalent magnitude. We investigated the relative ability of isoflurane vis-a-vis sevoflurane to maintain the target systolic blood pressure (SBP) in patients undergoing shoulder arthroscopic procedures.Methods:In a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…A few previous studies did focus on comparing haemodynamic effects of different anaesthetic agents, but in the LDP. [ 11 12 ] In contrast to previous findings, we observed equivalent SBPs, MBPs, and HR mean s with both agents in BCP arthroscopy. While rejecting the null hypothesis, we also checked whether sevoflurane could achieve haemodynamic status equivalent with isoflurane.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A few previous studies did focus on comparing haemodynamic effects of different anaesthetic agents, but in the LDP. [ 11 12 ] In contrast to previous findings, we observed equivalent SBPs, MBPs, and HR mean s with both agents in BCP arthroscopy. While rejecting the null hypothesis, we also checked whether sevoflurane could achieve haemodynamic status equivalent with isoflurane.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous study on shoulder arthroscopy in lateral decubitus position (LDP) demonstrated approximately 10 mmHg mean difference of SBP between group subjects when different techniques and inhalational agents were compared. [ 11 12 ] Based on this, we calculated the sample size for this study. A minimum of 16 patients were required in each group to detect a mean BP difference of 10 mmHg [power 80%, α = 0.05, with standard deviation (SD) of 10 in each group] assuming that differences of <10 mmHg would not be clinically significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation